Health Benefits, Quality and Safety of Fish in Kerala: Consumer Perception and Implications for Extension System - Rejula, K.; Sajeev, MV; Mohanty, AK (Indian Journal of Extension Education, 2025)
Knowledge about consumer perceptions on health benefits, quality and safety of fish is important for the development of targeted government interventions. The study conducted between December 2018 and March, 2020 explored and identified differences among consumers in Kerala, India according to their perceptions of nutritional and health benefits, quality and safety associated with fish consumption. By adopting purposive random sampling method,400 fish consumers from 2 coastal districts (Ernakulam and Kozhikode) and 2 inland districts (Kottayam and Palakkad) of Kerala was surveyed. While consumers had strong perception about the nutritional benefits of fish consumption, lower awareness was reported on specific health benefits from eating fish. Consumers had a very strong perception that fish quality is influenced by the mode of transport and local fish is having better quality than the fish brought from other states. Cleanliness of market was another concern. More than half of the consumers expressed their concern about absence of certification system to convey the freshness of fish. Majority of the consumers were having a medium perception about safety of fish. Significant difference was observed within perceptional statements about safety of fish and case of underestimating significant risks while overestimating others was also observed. Re-directing Government efforts in supply chain management of fish and in ensuring quality and safety of fish in every stage of the chain emerged as key concerns.